Mitigation measures, prevalence response and public mobility during the COVID-19 emergency - Noel Rapa (Central Bank of Malta, 2021)
In response to the rapid spread of the COVID-19 pandemic, national governments have implemented a range of mitigation measures designed to limit the transmission of the novel virus. In order to estimate the effects of these "non-pharmaceutical" policies, one needs to properly account for prevalence responses; self-imposed restrictions of individuals who trade-off the utility derived from social interactions against the risk of infection. We study the determinants of community mobility across the European Union during the COVID-19 crisis, focusing on government and self-imposed restrictions. Results indicate that timeseries breaks in all types of mobility were clustered across time and EU states, with the most discretionary types falling first and by the largest amounts. Mobility measures fall only after the escalation of government containment measures, with school closures and cancellation of public events preceding falls in all types of mobility across all EU states. This indicates that these two policies have led to an overall risk re-assessment by the general public leading to self-imposed yet not self-initiated falls in mobility. Finally, self-imposed restrictions occurring independently of government measures are responsible for a significant part in the fall of post-pandemic mobility in the EU.
Keywords: I12; I18; D70; D80; 330; COVID-19; Mobility; Government mitigation measures; Government response